PENGARUH EMPLOYEE ENGAGEMENT DAN KREATIVITAS TERHADAP KINERJA KARYAWAN PERUSAHAAN PELAYANAN JASA UNTUK PENUMPANG DAN BONGKAR MUAT KARGO (Fakultas Ekonomi dan Bisnis Universitas Faletehan, 2024)
The aim of this research is to investigate the impact of engagement and work creativity on improving employee performance in passenger and cargo service companies. This research has an explanatory type of research, with data collection using questionnaires and sampling techniques involving 42 respondents using saturated sampling techniques. The collected data was analyzed using SPSS software. Empirical results show that employee engagement does not have a significant influence on employee performance, while work creativity has a positive and significant influence on employee performance. Simultaneously, work engagement and creativity have a positive and significant influence on employee performance. This research formulates a conceptual model that focuses on engagement and creativity as factors in improving employee performance.